Between state and society: Local governance of forests in Malinau, Indonesia - Wollenberg, Eva Karoline; Moeliono, M.; Limberg, G.; Iwan, R.; Rhee, S.; Sudana, M. (Elsevier, 2006)
Decentralization in post-Soeharto Indonesia has not only changed state and society relations at the local level, but brought increased control over forests at the district level. Local social forces gained more influence because of their close relations with local government and acted to limit the local government. In this article we use the case of Malinau, East Kalimantan Indonesia to show how the new local autonomy over forests played a role in the rise of new local political orders.